Designing Learning for Tablet Classrooms - Walling, Donovan R. author. aut Link
XV, 137 p. 6 illus., 1 illus. in color.
Keywords: The versatile, cost-effective technology of the tablet computer has proved to be a good fit with the learning capabilities of today's students. Not surprisingly, in more and more classrooms, the tablet has replaced not only traditional print materials but the desktop computer and the laptop as well. Designing Instruction for Tablet Classrooms makes sense of this transition, clearly showing not just how and why tablet-based learning works, but how it is likely to evolve. Written for the non-technical reader, it balances elegant theoretical background with practical applications suitable to learning environments from kindergarten through college. A wealth of specialized topics ranges from course management and troubleshooting to creating and customizing etextbooks, from tablet use in early and remedial reading to the pros and cons of virtual field trips. And for maximum usefulness, early chapters are organized to spotlight core skills needed to negotiate the new design frontier, including: Framing the learning design approach. Analyzing the learning environment. Designing learning that capitalizes on tablet technology. Developing activities that match learning needs. Implementing the learning design. Conducting evaluations before, during, and after. This is proactive reading befitting a future of exciting developments in educational technology. For researchers and practitioners in this and allied fields, Designing Instruction for Tablet Classrooms offers limitless opportunities to think outside the box.